KINERJA DINAS KEPEMUDAAN DAN OLAHRAGA KOTA PEKANBARU STUDI KASUS BIDANG BINA KEPEMUDAAN - Rio Restu Anggara Putra; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Pekanbaru City Youth and Sports Agency has the responsibility to provide guidance and youth training as a form of youth empowerment. It is stated in Government Regulation Number 41 of 2011 concerning Development of Youth Entrepreneurship and Leadership, and Provision of Youth Infrastructure and Facilities. The phenomenon in this study are the low guidance and empowerment of youth, inadequate budget and minimal facilities and infrastructure. The purpose of this study is to determine the performance and factors that hamper the performance of the Department of Youth and Sports of the City of Pekanbaru in Youth Development. This research used descriptive qualitative method, data collected through observation and interviews. This research was conducted using the theory of performance by Mahsun, which consists of inputs, processes, outputs, results, benefits and impacts. The conclusions of this study are the performance of the Department of Youth and Sports in the Youth Development Sector has not been running optimally. This is indicated by the lack of budget needed, then the low development and empowerment of youth and the lack of youth facilities and infrastructure. Keywords: Performance, Youth, Sports